A Decade Experience on Severe Combined Immunodeficiency Phenotype in Oman, Bridging to Newborn Screening - Al Sukaiti, Nashat; Ahmed, Khwater; Alshekaili, Jalila; Al Kindi, Mahmood; Cook, Matthew C.; Farsi, Tariq Al (Frontiers in Immunology, 2021)
Introduction: Severe combined immunodeficiency (SCID) results from various monogenic defects that impair immune function and brings on early severe and life-threatening infections. The main stay of treatment for SCID is hematopoietic stem cell transplant (HSCT) with near normal survival at 5 years for an early transplant done at or before the age of 3.5 months of life and the patient is maintained free of infections. Although overall rare, it constitutes a major burden on affected children, their families and on the health system especially in communities with a high rate of consanguinity where incidence and prevalence of recessive inborn errors of immunity (IEI) are expected to be high. Method: Here, we report the clinical, immunological, and molecular findings in 36 children diagnosed with SCID from a single tertiary center in Oman for the last decade. Results: We observed a median annual incidence rate of 4.5 per 100,000 Omani live births, and 91.7% of affected children were born to consanguineous parents. Twenty-three children (63.9%) fulfilled the criteria for typical SCID. The median age at onset, diagnosis and diagnostic delay were 54, 135 and 68 days respectively. The most common clinical manifestations were pneumonia, septicemia and chronic diarrhea. Eleven children (30.6%) have received hematopoietic stem cell transplant (HSCT) with a survival rate of 73%. The most frequent genetic cause of SCID in this cohort (n=36) was (RAG-1), encoding for recombination activating gene (n=5, 13.9%). Similarly, Major histocompatibility complex type II deficiency accounted for (n=5, 13.9%) of our cohort. Conclusion: Our report broadens the knowledge of clinical and molecular manifestations in children with SCID in the region and highlights the need to initiate newborn based screening program (NBS) program.